A implementação do método de melhoria de resultados (MMR): implicações e perspectivas de atuação do gestor escolar na região do Pontal do Paranapanema – São Paulo - LEAL, Lindsay da Silva Cruz (2021)
The present research aimed to analyze what implications the Results Improvement Method (MMR) – brought to the daily actions, developed by the manager within the school. This method is part of the “Gestão em Foco” program, whose goal is to promote the continuous improvement of the quality of learning based on the results of the Education Development Index of the State of São Paulo (IDESP). The research adopted a qualitative, descriptive and exploratory approach, using semi-structured interviews and analysis of documents related to the MMR. The interviews were mediated by technology, due to the COVID-19 pandemic, being carried out during the month of August 2021. Five school managers who are part of the Education Board (DER) – Mirante do Paranapanema Region were chosen as participants in this research. They experienced the implementation of the Results Improvement Method in 2018. The criterion for choosing this audience aimed at the possibility of developing a discussion addressing aspects of how the school was managed before and what changed after the implementation of the MMR, as well as understanding the implementation process and the training of management teams carried out by members of the Education Board. The research discusses what the implementation of this method has changed in the practice of managers, with regard to their work routine and the search for educational results presented by students based on this policy of the São Paulo government, whose objective is to advance in the quality of education in public schools through the application of the MMR. The research placed the aforementioned method in the broader context of educational reforms and related it to new management paradigms based on the principles of New Public Management (NGP), contributing to the understanding of ideologies implied in a historical process of transformation of school management in the state of São Paulo from the neoliberal rhetoric. The results showed that a) managers understand the MMR and its structuring; b) they had difficulties in adapting themselves to the new demands imposed by the method; c) managers highlight the excessive bureaucracy of the MMR and the consequent work overload brought about by its implementation; d) the performance of students, in terms of learning did not show significant improvement since the method was implemented; e) before the implementation of the MMR, the school already had data analysis strategies with a view to actions to improve learning. It is concluded that the present research stands out for its relevance in terms of the investigation carried out on the implementation of the MMR, which allowed a detailed analysis of this recent São Paulo educational policy to be unveiled. In addition, the research allowed the verification of the negative impacts caused in the performance of managers with the implementation of business methods inserted in the educational context, revealing that the MMR potentiated the bureaucratic character imposed on the performance of the school manager and also showed that, even in the face of excessive control, the method did not proved capable of offering what it proposes through its official texts, which advocate as main objective the improvement of the quality of education measured through the results of external evaluations, with emphasis on the State School Performance Evaluation System de São Paulo – SARESP whose data are provided through IDESP. The analyzes show that in schools where there were pedagogical advances, these advances were not significant.